Towards uniformly oriented diatom frustule monolayers: Experimental and theoretical analyses - Li, Aobo (Microsyst Nanoeng, 2016)
Diatoms are unicellular, photosynthetic algae that are ubiquitous in aquatic environments. Their unique, three-dimensional (3D) structured silica exoskeletons, also known as frustules, have drawn attention from a variety of research fields due to their extraordinary mechanical properties, enormous surface area, and unique optical properties. Despite their promising use in a range of applications, without methods to uniformly control the frustules’ alignment/orientation, their full potential in technology development cannot be realized. In this paper, we realized and subsequently modeled a simple bubbling method for achieving large-area, uniformly oriented Coscinodiscus species diatom frustules. With the aid of bubble-induced agitations, close-packed frustule monolayers were achieved on the water–air interface with up to nearly 90% of frustules achieving uniform orientation. The interactions between bubble-induced agitations were modeled and analyzed, demonstrating frustule submersion and an adjustment of the orientation during the subsequent rise towards the water’s surface to be fundamental to the experimentally observed uniformity. The method described in this study holds great potential for frustules’ engineering applications in a variety of technologies, from sensors to energy-harvesting devices.